2013
DOI: 10.1016/j.juro.2013.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Pad Count is a Poor Measure of the Severity of Urinary Incontinence

Abstract: There was little correlation between the number of pads used and the severity of urinary incontinence (r=0.26). These data suggest that pad count should not be used as an objective measure of incontinence severity. Instead, pad weight on a 24-hour pad test should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 13 publications
4
34
2
Order By: Relevance
“…Currently, several studies reported that pad count is a poor measure of the severity of urinary incontinence. 7,14,15 Although previous studies did not identify the reason why there was little correlation between the pad count and severity of urinary incontinence, one of the possible reasons drawn from the present data was that patients after RARP wore various configurations and sizes of pads unrelated to the volume of urinary incontinence. Hence, pad count could not be used as an objective measure of incontinence severity after RARP, at least in the early postoperative period.…”
Section: Discussioncontrasting
confidence: 69%
“…Currently, several studies reported that pad count is a poor measure of the severity of urinary incontinence. 7,14,15 Although previous studies did not identify the reason why there was little correlation between the pad count and severity of urinary incontinence, one of the possible reasons drawn from the present data was that patients after RARP wore various configurations and sizes of pads unrelated to the volume of urinary incontinence. Hence, pad count could not be used as an objective measure of incontinence severity after RARP, at least in the early postoperative period.…”
Section: Discussioncontrasting
confidence: 69%
“…However, in the subgroup of men with PPI using protections, the perceived number of pads used were recently found highly correlated with the severity of incontinence on a 24-h pad test in a prospective evaluation [15 && ]. These data come against other assumptions by Tsui et al [16], who estimated that pad use was rather badly correlated with incontinence severity. However, their retrospective analysis only included a limited number of men.…”
Section: Clinical Datacontrasting
confidence: 45%
“…14, 22 We saw a decrease in number of pads used per day and night over time. However, in our anecdotal experience, and considering the variability in how patients use pads, we did not include pad number in our definition of continence.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 90%